1987
DOI: 10.3379/jmsjmag.11.s1_361
|View full text |Cite
|
Sign up to set email alerts
|

TEMPERATURE DEPENDENCE OF FARADAY ROTATION FOR Bi-SUBSTITUTED Tb IRON GARNET FILMS

Abstract: Temperature dependence of Faraday rotation, which causes degradation of isolation at high or low temperature for an optical isolator, was rreasured at 1. 3,um and 0.78,um wavelength together with saturation magnetization and optical transparency for epitaxially grown (TbBi)3FeS012 and ('!bLaBi) 3FeS012 films. Tenperature dependence of faraday rotation for these films w=re smaller than those for (GdBi)3(FeAlGa)S012 films and (GdBi)3FeS012 bulk single crystals.Particularly, thick '!b2.2LaO.2BiO 6FeS012 films sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In experimental, several authors reported the TDF Faraday rotator (FR) made by (Tb,Bi)3Fe5O12 for practical applications [1][2][3][4][5]. In experimental, several authors reported the TDF Faraday rotator (FR) made by (Tb,Bi)3Fe5O12 for practical applications [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental, several authors reported the TDF Faraday rotator (FR) made by (Tb,Bi)3Fe5O12 for practical applications [1][2][3][4][5]. In experimental, several authors reported the TDF Faraday rotator (FR) made by (Tb,Bi)3Fe5O12 for practical applications [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that a relatively low Bi content suppressed the FR and required a critical thick LPE-grown film over 1500 m for optical isolator applications wavelength at 1550nm for example, which induced the degradation of the crystal uniformity and the optical transparency [1]. They indicated that a relatively low Bi content suppressed the FR and required a critical thick LPE-grown film over 1500 m for optical isolator applications wavelength at 1550nm for example, which induced the degradation of the crystal uniformity and the optical transparency [1].…”
Section: Introductionmentioning
confidence: 99%
“…TbIG has a Faraday rotation in 1100-1550 nm wavelength range of ≈ +270 to +1000° cm −1 . [23][24][25] Bi-substituted TbIG has been grown by liquidphase epitaxy and flux methods [23][24][25][26][27] or sol-gel methods, [28] and more recently thin films of Ce-and Bi-substituted TbIG (CeTbIG, BiTbIG) were grown on Si by sputtering. [29][30][31][32][33][34] Sputtered BiTbIG with Bi substitution of 14% of the Tb sites has a Faraday rotation of ≈−500° cm −1 at 1550 nm, [29] the same sign as that of CeYIG, which at 1550 nm wavelength had a Faraday rotation of at least −3700° cm −1 .…”
mentioning
confidence: 99%